Produce D-allulose from non-food biomass by integrating corn stalk hydrolysis with whole-cell catalysis - Jia, Qing; Zhang, Hui; Zhao, Anqi; Qu, Lingbo; Xiong, Wenlong; Alam, Md. Asraful; Miao, Jixing; Wang, Weigao; Li, Feihu; Xu, Jingliang; Lv, Yongkun (Frontiers in Bioengineering and Biotechnology, 2023)
D-allulose is a high-value rare sugar with many health benefits. D-allulose market demand increased dramatically after approved as generally recognized as safe (GRAS). The current studies are predominantly focusing on producing D-allulose from either D-glucose or D-fructose, which may compete foods against human. The corn stalk (CS) is one of the main agricultural waste biomass in the worldwide. Bioconversion is one of the promising approach to CS valorization, which is of significance for both food safety and reducing carbon emission. In this study, we tried to explore a non-food based route by integrating CS hydrolysis with D-allulose production. Firstly we developed an efficient Escherichia coli whole-cell catalyst to produce D-allulose from D-glucose. Next we hydrolyzed CS and achieved D-allulose production from the CS hydrolysate. Finally we immobilized the whole-cell catalyst by designing a microfluidic device. Process optimization improved D-allulose titer by 8.61 times, reaching 8.78 g/L from CS hydrolysate. With this method, 1 kg CS was finally converted to 48.87 g D-allulose. This study validated the feasibility of valorizing corn stalk by converting it to D-allulose.